THE CONTRIBUTIONS OF LANDSCAPE TO THE URBAN AND ENVIRONMENTAL PLANNING PROCESS AND TO THE INTEGRATED MANAGEMENT OF THE HYDROGRAPHIC BASIN - Correia, Elizabeth de Fátima; Nunes, Nilo; Nunes, Laís Samira Correia; Guandique, Manuel Enrique Gamero (Seven Editora, 2026)
In the current scenario of environmental manipulation and landscape interventions, the adoption of a new paradigm for urban and environmental planning becomes urgent, raising the question of how landscape planning, design, and architecture can contribute to the urban and environmental planning of the watershed. The objectives consist of investigating the theoretical and methodological concepts applied in landscape planning, design, and architecture; contributing to urban and environmental planning, using the watershed as the basis of this process; identifying proposals, experiences, and projects carried out on this theme; and contributing to broadening conceptual reflection and deepening the debate on integrated landscape management. The methodology was exploratory, involving the collection and compilation of documents and texts; reading, studying, and analyzing the selected material; and textual organization. It was concluded that landscape planning, design, and architecture contribute to the urban and environmental planning of the hydrographic basin through the application of environmental solutions such as connectivity, biodiversity, water governance, strengthening urban resilience, and the interaction of nature with people, as living, adaptive, and sustainable solutions to the urban and environmental challenges of contemporary cities.